Upaya Perlindungan Hukum dan Pemulangan Dalam Kasus Tindak Pidana Perdagangan Orang di Myanmar (Legal Protection And Return Efforts of Human Trafficking People In Myanmar Cases) - Sabrina, Fadiah Tarisa; Prasetyo, Handoyo (Media Hukum Indonesia (MHI), 2024)
Everyone desires a prosperous life, but challenges in the modern era are increasingly diverse, encompassing economic, educational, and cultural issues. Poverty and low education levels are the main drivers for people to improve their welfare. In 2016, more than 9 million Indonesian migrant workers were recorded working abroad, contributing remittances amounting to Rp 118 trillion. The majority of migrant workers come from poor rural areas with low education levels, and many work non-procedurally. This condition is often exploited by human traffickers. Human trafficking is a transnational crime that occurs across borders. In Indonesia, this crime is regulated by Law No. 21 of 2007 on the Eradication of the Crime of Human Trafficking, which provides protection and restitution for victims. However, law enforcement is still lacking. Southeast Asia is a region with high human trafficking activity, where ASEAN and the UN have made agreements to address it. The recent case in Myanmar shows the gap between regulations and practices on the ground. Several Indonesian citizens were smuggled into Myanmar, deceived, forced, and exploited. The Indonesian government is trying to repatriate them, but it is hampered because the online scamming company is located in a conflict area. This shows that despite various legal instruments, there are still significant challenges in law enforcement related to human trafficking.